Semi Lobar Holoprosencephaly with Vertebral Segmentation Defects - RAI, Birendra; SHARIF, Farhana (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Rai B, Sharif F. Semi Lobar Holoprosencephaly with Vertebral Segmentation Defects. Iran J Child Neurol. Summer 2017; 11(3):61-65. Abstract Holoprosencephaly is the most common embryonic brain defect. Foetuses who survive during intrauterine life are born with varying grades of brain and facial deformities. Extra craniofacial manifestations are common. Vertebral segmentation defects are rarely seen with holoprosencephaly, mainly in association with holoprosencephaly diencephalic hamartoblastoma (HDH) association. A female infant was born at term by normal delivery. Birth head circumference was below the 3rd percentile. Antenatal scan had showed microcephaly as the only abnormality. Physical examination revealed microcephaly, ocular hypotelorism, left ear skin tag and short neck. MRI of the brain showed semilobar holoprosencephaly. Neck radiograph revealed gross vertebral segmentation defect involving cervical and upper thoracic vertebrae. She had initial feeding difficulties. She showed severe global developmental delay and had underlying central diabetes insipidus. Vertebral segmentation defect is rare in holoprosencephaly. References 1. Shiota K, Yamada S, Komada M, et al. Embryogenesis of holoprosencephaly. Am J Med Genet A 2007; 43A(24):3079-87. 2. Verloes A, Gillerot Y, Langhendries JP, et al. Variability versus heterogeneity in syndromal hypothalamic hamartoblastoma and related disorders: review and delineation of the cerebro-acro-visceral early lethality (CAVE) multiplex syndrome. Am J Med Genet 1992 Jul 1;43(4):669-77 3. Guimiot F, Marcorelles P, Aboura A, et al. Giant diencephalic harmartoma and related anomalies: a newly recognized entity distinct from the Pallister-Hall syndrome. Am J Med Genet A 2009; 149A(6):1108-15. 4. Castori M, Douzgou S, Silvestri E, et al. Reassessment of holoprosencephaly-diencephalic hamartoblastoma (HDH) association. Am J Med Genet A 2007; 143(3):277- 84. 5. Croen LA, Shaw GM, Lammer EJ. Holoprosencephaly: epidemiologic and clinical characteristics of a California population. Am J Med Genet 1996; 64(3):465-72. 6. Christèle Dubourg, Claude Bendavid, Laurent Pasquier, et al. Holoprosencephaly. Orphanet J Rare Dis 2007; 2: 8. Published online 2007 February 2. 7. Orioli IM, Castilla EE. Epidemiology of holoprosencephaly: Prevalence and risk factors. Am J Med Genet C Semin Med Genet 2010; 154C(1):13-21. 8. Plawner LL, Delgado MR, Miller VS, et al. Neuroanatomy of holoprosencephaly as predictor of function: beyond the face predicting the brain. Neurology 2002; 59(7):1058- 66. 9. Barr M Jr, Cohen MM Jr. Holoprosencephaly survival and performance. Am J Med Genet 1999; 89(2):116-20. 10. Lewis AJ, Simon EM, Barkovich AJ, et al. Middle interhemispheric variant of holoprosencephaly: a distinct cliniconeuroradiologic subtype. Neurology 2002; 59(12):1860-5. 11. Bellone S, De Rienzo F, Prodam F, et al. Etiopathogenetic advances and management of holoprosencephaly: from bench to bedside. Panminerva Med 2010; 52(4):345-54. 12. Wallis D, Muenke M. Mutations in holoprosencephaly. Hum Mutat 2000; 16(2):99-108. 13. Miller EA, Rasmussen SA, Siega-Riz AM, et al. National Birth Defects Prevention Study. Risk factors for nonsyndromic holoprosencephaly in the National Birth Defects Prevention Study. Am J Med Genet C Semin Med Genet 2010; 154C(1):62-72. 14. Cohen MM Jr, Shiota K. Teratogenesis of holoprosencephaly. Am J Med Genet 2002; 109(1):1-15. 15. Kline-Fath BM, Calvo-Garcia MA. Prenatal imaging of congenital malformations of the brain. Semin Ultrasound CT MR 2011; 32(3):167-88.